2014
DOI: 10.17796/jcpd.39.1.e72570275387527r
|View full text |Cite
|
Sign up to set email alerts
|

Resin Penetration in Artificial Enamel Carious Lesions after Using Sodium Hypochlorite as a Deproteinization Agent

Abstract: Objectives: To study the degree of penetration of an adhesive resin in artificial enamel carious lesions after using sodium hypochlorite as deproteinization agent. Study design: Twenty included human third-molars, extracted for surgical indication, were used. Artificial lesions were created in the buccal and lingual sides of each specimen through a cycle of demineralization-remineralization. Samples were then incubated in human saliva for 7 days at 37 ° C. After surface cleaning, lesions and the peripheral sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…The enamel surface can be deproteinized with NaClO before bonding to increase the penetration of the adhesive into the enamel and further improve the bond strength. Thus, prior to acid etching, 5.25% NaClO is applied onto the enamel surface for 1 min to improve the etching property [ 11 , 12 ]. The pH of NaClO is similar to that of calcium hydroxide, which reacts with OH– to form NaOH and HClO.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The enamel surface can be deproteinized with NaClO before bonding to increase the penetration of the adhesive into the enamel and further improve the bond strength. Thus, prior to acid etching, 5.25% NaClO is applied onto the enamel surface for 1 min to improve the etching property [ 11 , 12 ]. The pH of NaClO is similar to that of calcium hydroxide, which reacts with OH– to form NaOH and HClO.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, sodium hypochlorite (NaClO) solution provides specific properties such as disinfection and cleaning of root canals from impurities and organic substances. Previous studies have shown that pretreatment of enamel surface with NaOCl can increase the degree of penetration of adhesives into the enamel [ 11 , 12 ]. Owing to the deproteinization of the enamel surface by NaClO, suitable acid etching is required to achieve better bond strength between the bracket and enamel [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…And beyond that, our study showed that when the enamel was treated with or without 5.25% NaOCl, no significant difference was observed in PD of CSB and PBN except for SB2 and SBU. However, the previous findings indicated that using 5.25% NaOCl for 60 s can improve the PD of the sealing resin significantly 27) . It revealed that the application of 5.25% NaOCl got rid of protein from the surface and increased porosity 24) .…”
Section: Discussionmentioning
confidence: 85%
“…Previous research indicated there was a remarkably greater protein content by weight in fluorotic enamel and inter-rod areas contained more organic material than enamel rods 25,26) . In addition, NaOCl not only removed the excess protein content from the enamel surface but also got rid of salivary proteins and organic material from saliva which was adsorbed in the surface of the teeth and might disturb acid etching and penetration of the resin 14,27) . Some studies also revealed that the application of NaOCl in 60 s increased the type 1-2 etching pattern of enamel 13,25,28) .…”
Section: Discussionmentioning
confidence: 99%
“…17,18 On the other side, the application of sodium hypochlorite after acid etching during the process of surface pretreatment has been discussed in literature proving its effect in enhancing the shear bond strength values, increasing the penetration and retention of adhesive resins by 20.1% compared to the conventional way of only acid etch the enamel surface, and affects the surface roughness of enamel surface with the minimum percentage of surface loss. [19][20][21][22] Upon all these findings regarding using sodium hypochlorite as an enamel surface pretreatment and self-assembling peptide remineralization capabilities, it was found thought-provoking to study the effect of applying sodium hypochlorite as a deproteinizing agent after acid etching of demineralized sound enamel structure with the aim of minimizing loss of surface enamel, exposure of more reactive enamel, and creation of porosities that may allow for more rapid uptake of remineralizing solution as assessed by surface microhardness (SMH) testing.…”
Section: Introductionmentioning
confidence: 99%